2021
DOI: 10.1016/j.xrrt.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Primary reverse shoulder replacement with a short stem: A systematic literature review

Abstract: Background: Total shoulder arthroplasty implant designs have continued to evolve over the years. One recent change has been the shortening of the humeral component to preserve bone stock and to facilitate revision surgery. Despite promising clinical results, radiographic bone adaptions occur frequently in short-stem total shoulder arthroplasty, and limited data exist on short-stem reverse shoulder arthroplasty (RSA). The purpose of this systematic review was to provide an overview about the functional and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…A study by Ascione et al included various diagnoses and a comparable revision rate of 10.0% was found after the implantation of the same type of short stem RSA in 100 cases with a mean follow-up of 32.6 months. Also, the present analysis revealed that the mean time until revision was 53.4 months after the implantation of RSA, which is more than the maximum FU of the most published studies on short stem RSA [ 44 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A study by Ascione et al included various diagnoses and a comparable revision rate of 10.0% was found after the implantation of the same type of short stem RSA in 100 cases with a mean follow-up of 32.6 months. Also, the present analysis revealed that the mean time until revision was 53.4 months after the implantation of RSA, which is more than the maximum FU of the most published studies on short stem RSA [ 44 ].…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, the study found a revision rate of 12.7% (15 cases) after short stem RSA. Compared to a 4.9% revision rate after short stem RSA in a systematic review with an average follow-up of 20–99.6 months among 10 included studies, the revision rate in this study is somewhat higher [ 44 ]. Also, the reported revision rate in this study appears to be higher than revision rates after standard stem RSA [ 5 , 14 , 17 , 22 , 41 , 50 ].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 11 Longer diaphyseal stems increase fixation and stability of the implant while compromising increased bone stock in the setting of revision surgery and potentially leading to higher rates of stress shielding as well as increased osteolysis in the primary setting. 13 , 24 Conversely, short-stem implants not achieving adequate metaphyseal fixation can predispose to component loosening and malalignment as demonstrated in TSA. 3 , 8 In some cases, a short-stem implant combining both diaphyseal and metaphyseal fixation could avoid this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Authors have reported short-stemmed implants (size, 60-65 mm) to perform with comparable patient reported outcomes and range of motion compared to standard length with similar postoperative alignment, radiographic signs of loosening, and survival free of revision at short-term follow-up. 12 , 24 However, mid- and long-term follow-ups of short-stem RTSA data remain scarce. Although uncommon, short stems exhibit a higher stress level at the metaphysis increasing the risk of fracture in that region.…”
Section: Discussionmentioning
confidence: 99%